Cytopenia in T Cell Subsets: A Predictor of Severe COVID-19 - Giti, Susane; Bhuiyan, Mohammed Nuruzzaman; Muntasir Hossen, Mohammad Shameem; Rahman, Md Moshiur; Afroj, Nadia (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: The outbreak of Coronavirus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has posed great threat to human health. T cells play a critical role in antiviral immunity but their numbers and functional state in COVID-19 patients remain largely unclear. The present study was carried out at Armed Forces Institute of Pathology (AFIP), Dhaka to assess the degree of cytopenia of T cell subsets in COVID 19 and its association with severity of the disease. The aim of this study is to assess the degree of reduction of T cell subsets in both non severe and severe COVID 19 patients. Methods: Total 100 patients having positive result of RTPCR for SARS-CoV-2 and lymphopenia were recruited for this study. Patients were grouped as ICU and non- ICU according to the severity of clinical conditions, consisting of 50 patients in each group. Data of T cell subsets were obtained by flow cytometric analysis of peripheral blood using monoclonal antibodies. Results: In this study, the absolute value of CD3+ T cells was below the normal range in 47 (94%) ICU patients. Compared to the non-ICU group, the median absolute value of CD3+ T cells was significantly lowered (P=0.019) in the ICU group. The absolute value of CD4+ T cells was also below the normal range in 91patients (91%). All the patients in the ICU group showed low CD4+ T cell counts. Moreover, a significantly lower median absolute value of CD4+ T cells was observed in the ICU group compared to the non-ICU group (P = 0.004). The absolute value of CD8+ T cells was below the normal range in 64 patients (64%). Similar to CD4+ T cells, compared to the non-ICU group, the median absolute value of CD8+ T cells was significantly lower in the ICU group (P = 0.028). Conclusion: Significant reduction of T cell subsets occurs in severe COVID-19. Flow cytometric analysis of T cell subsets in COVID 19 patients with absolute lymphopenia can guide the physician to predict the severe outcome of the disease. J Bangladesh Coll Phys Surg 2022; 40: 217-222